2005
DOI: 10.3748/wjg.v11.i48.7631
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and effects of polymorphic RANTES gene alleles in HIV/HCV coinfection – A prospective cross-sectional study

Abstract: All three RANTES polymorphisms showed increased frequencies of the variant allele exclusively in patients with HIV monoinfection. The finding that the frequencies of these alleles remained unaltered in HIV/HCV coinfected patients suggests that HCV coinfection interferes with selection processes associated with these alleles in HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…The frequency of the RANTES In1.1C allele in this study population (20%) is lower than what has been observed among Asians (28%) [15], but higher than that among Caucasians (10%) [31]. The occurrence of the RANTES -403A allele in Zimbabweans (44%) was higher than that among Caucasians (16%) [32] but was comparable to that observed among Asians (40%) [33]. The RANTES In1.1T>C polymorphism is located in an intronic regulatory sequence and the In1.1C variant is associated with down-regulation of RANTES expression [34], resulting in fewer chemokines available to inhibit HIV binding or to internalize CCR5 receptors on T-cells, thus favoring HIV infection.…”
Section: Chemokine Receptor Variants and Their Association With Hiv Icontrasting
confidence: 41%
“…The frequency of the RANTES In1.1C allele in this study population (20%) is lower than what has been observed among Asians (28%) [15], but higher than that among Caucasians (10%) [31]. The occurrence of the RANTES -403A allele in Zimbabweans (44%) was higher than that among Caucasians (16%) [32] but was comparable to that observed among Asians (40%) [33]. The RANTES In1.1T>C polymorphism is located in an intronic regulatory sequence and the In1.1C variant is associated with down-regulation of RANTES expression [34], resulting in fewer chemokines available to inhibit HIV binding or to internalize CCR5 receptors on T-cells, thus favoring HIV infection.…”
Section: Chemokine Receptor Variants and Their Association With Hiv Icontrasting
confidence: 41%
“…The two CCL5 promoter polymorphisms, −403G/A and −28C/G, have been shown to be associated with many infectious diseases such as HIV, hepatitis and TB, (An et al. , 2002; Ahlenstiel et al. , 2005; Chu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of RANTES In1.1C was carried out by previously described protocol [Ahlenstiel et al, 2005] using forward primer: 5 0 -CCT GGT CTT GAC CAC CAC A-3 0 and reverse primer: 5 0 -GCT GAC AGG CAT GAG TCA GA-3 0 . A 343-bp fragment spanning position In1.1C was amplified from extracted genomic DNA.…”
Section: Polymerase Chain Reaction and Sequencingmentioning
confidence: 99%